Oxygen consumption during concurrent training: influence of intra-session exercise sequence and aerobic exercise modality - Ferrari, R.; Alberton, C.; Pinto, S.; Cadore, E.; Pinto, R.; Kruel, L. F. (Biology of Sport, 2018)
To compare the acute effects of different intra-session exercise sequences and aerobic exercise modalities during concurrent training sessions on oxygen consumption (VO2) and energy expenditure (EE) in young women. Eleven young women volunteered to participate in this study and underwent tests of their dynamic strength and a maximal incremental test on both the treadmill and cycle ergometer. Four concurrent training sessions were performed: resistance-running (RRu), resistance-cycling (RC), running-resistance (RuR) and cycling-resistance (CR). The aerobic exercise lasted 30 minutes and was performed at a heart rate equivalent to 95% of the second ventilatory threshold. The resistance exercise lasted approximately 21 minutes and consisted of 4 sets of 10 RM in each exercise. The VO2 was continuously evaluated through the portable gas analyser. No differences were found in the VO2 between the intra-session exercise sequence independently of aerobic modality (i.e., RRu vs. RuR, and RC vs. CR), and the sessions with the running aerobic exercise showed greater VO2 than sessions using cycling aerobic exercise in both exercise sequences (VO2aerobic (ml · kg-1 · min-1) - RRu: 27.5; RuR: 27.1; RC: 20.2; CR: 20.8). The present study showed that the intra-session exercise sequence during concurrent training does not influence VO2. However, the optimal combination of resistance and aerobic exercise should include running in order to increase VO2 and optimize EE.